Identification of Silicification Types in Carbonate Reservoirs Based on Elemental Capture Spectroscopy Logging and Nuclear Magnetic Resonance Logging - WANG Shixin; YANG Zhiguo; LIU Xiaoliang; ZHAO Deli; LI Huaibiao; LIU Houwu (Cejing jishu)
Silicification is commonly developed in Santos basin, Brazil, which has great effect on reservoir property. On the basis of previous studies on silicification in this area, using conventional logging, element capture spectroscopy logging and nuclear magnetic resonance logging as the main means, combined with reservoir physical property data, X-ray diffraction data and thin slice data, the genetic types of silicification are further subdivided, and the effects of different silicification on reservoir physical properties are analyzed. The typical logging response characteristics and discrimination methods of different silicification processes are summarized. It shows that different silicification types have different influence on reservoir property. The physical properties of the early rock a type have little influence on the reservoir, the physical properties of the early rock b type and the post-hydrothermal b type deteriorate with the increase of silica content, and the physical properties of the post-hydrothermal a type become extremely poor, which is not an effective reservoir in this area. On the basis of quantitative calculation of formation silicon content by elemental capture spectroscopy logging, the silicification types of carbonate reservoir can be identified by comprehensive analysis of conventional logging and nuclear magnetic resonance logging curves characteristics. This study has reference significance for other similar areas to identify silicification types.